KAJIAN PERAN BAHAN PEMUTIH NATRIUM PIROPOSPHATE (Na2H2P2O7) TERHADAP PROSES PEMBUATAN TEPUNG UBI JALAR - Welasih, Tjatoer; Hapsari, Nur (UPN VETERAN JAWA TIMUR, 2011)
The study aims to determine the effect of bleaching on sweet potato flour. The specified condition is weight 300 g sweet potato, with white colour and Piroposphate Sodium (Na2H2P2O7) concentration: 0; 0.3; 0.6; 0.9; 1.2 g And soaking time: 5; 10; 15; 20; 25 minutes. The results obtained the best degrees of color at concentration of 1.2 g with 25-minute immersion time of 30 TCU, the lowest obtained at concentrations of 0 g 0 minutes by long immersion in the amount of 5.0 TCU. To obtain the best conditions of water content at a concentration of 1.2 grams with a long soaking 25 minutes in the amount of 11.78%, the lowest obtained at concentrations of 0 g 0 minutes by long immersion in the amount of 7.8%. For the largest starch content was obtained at a concentration of 0.6 g with 25-minute long immersion in the amount of 28.54%, the lowest obtained at concentrations of 0 g to 25 minutes long immersion in the amount of 26.66%.Keywords: Sodium Piroposphate, flour, sweet potatoes, bulbs, bleach